2009
DOI: 10.1111/j.1468-2443.2009.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure for Japanese Multinational and Domestic Corporations*

Abstract: Our study examines whether there are systematic differences in standard leverage determinants for a sample of Japanese multinational (MNCs) and domestic corporations (DCs). We find that on a univariate basis Japanese MNCs differ significantly on most variables relative to Japanese DCs. These variables include leverage, age, collateral value of assets, free cash flows, foreign exchange risks, growth, non-debt tax shields, political risks, profitability and size. Business risks are not found to be significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 50 publications
5
67
0
1
Order By: Relevance
“…The more recent body of literature indicates that the firm-specific and countryspecific factors in firms' leverage choices differ across countries (for example, Jong et al, 2007;Akhtar and Oliver, 2009;Delcoure, 2007), and particularly focuses on the effect of state ownership and regional institutions on firms' capital structure decisions, and more especially on the role of Chinese state ownership. Brandt and Li (2003) and Cull et al (2009) found evidence suggesting that private firms in China are denied access to bank loans and that they resort to more expensive trade credits instead.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The more recent body of literature indicates that the firm-specific and countryspecific factors in firms' leverage choices differ across countries (for example, Jong et al, 2007;Akhtar and Oliver, 2009;Delcoure, 2007), and particularly focuses on the effect of state ownership and regional institutions on firms' capital structure decisions, and more especially on the role of Chinese state ownership. Brandt and Li (2003) and Cull et al (2009) found evidence suggesting that private firms in China are denied access to bank loans and that they resort to more expensive trade credits instead.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Firms with higher non debt tax shields are expected to have lower debt ratio. Thus non debt tax shields are negatively related with capital structure (Akhtar & Oliver, 2005).…”
Section: Literature Reviewmentioning
confidence: 95%
“…HI.1: Agency problems are positively related to the change in debt level. Altman (1968), Douglas and Finnerty (1997), and Akhtar and Oliver (2009) find that the probability of bankruptcy has a negative influence on the change in debt level. A firm that has a high level of possibility of bankruptcy would be difficult to get financing from debt as its cash flows are deemed not sufficient to pay the interest and principal of debt.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%